INTERNATIONAL TERRORISM AS AN INSTRUMENT OF POLITICAL STRUGGLE AND OF INJURY TO INTEGRATIONAL LAW - Lessa, Pablo Henrique Cordeiro; Cervantes, Nélida Astezia Castro; Forte, Ana Rízzia Cunha Cordeiro; de Sousa, Maria Iracema Pinho; Lessa, Pietra Cordeiro; Alencar, Sérgio Ricardo Ribeiro (ARACÊ, 2024)
Debate international terrorism, that occurs since old ages, when it was committed against the monarch, has been classified in modern age as a political crime that is committed against the State. However, even if it had occurred since ancient times, only after the international repercussion of the attacks on September 11th, 2001, the issue gained practice importance in the International Agenda. Such evolution took many researches to describe the economic aspect, which tends to be directly affected, especially considering the State intervention is usually taken to avoid economic chaos and to make the State able to reach its function of Social Welfare keeper. This has a great clamor on populist governments, that want to demonstrate force and competence against Terrorism. Such a practice instils in people's minds the association of terrorism with specific ethnic and religious groups, indirectly building a nationalist mentality that tends to be exploited by populists deeply.  This creates a bad view over resistant movements from the Third World Countries, as TWAIL. Thus, a stronger State tends to be formed, and the consequences of this are dangerous and unknown.